Global health economics shaping health policy in low- and middle-income countries - Moreno-Serra, Rodrigo; Revill, Paul; Sculpher, Mark J.; Suhrcke, Marc (New Jersey World Scientific Publishing, 2019)
Provides up-to-date research on the theories and applications of health economics. Presents approaches to health economics developed at the University of York which are recognized for their high quality and distinction. Possesses practical tools and methods in dealing with health care challenges faced by LMIC countries"--
Contents: PART 1: Health Care Provision and Health - Chapter 1: Assessing the Impact of Health Care Expenditures on Mortality Using Cross-Country Data / Ryota Nakamura, James Lomas, Karl Claxton, Farasat Bokhari, Rodrigo Moreno-Serra and Marc Suhrcke - - PART 2: Economic Evaluation - Chapter 2: Allocating Scarce Resources - Tools for Priority Setting / Jessica Ochalek, Paul Revill and Micheal Drummond - - Chapter 3: Cost-Effectiveness Thresholds: Guiding Health Care Spending for Population Health Improvement / Paul Revill, Jessica Ochalek, James Lomas, Ryota Nakamura, Beth Woods, Alexandra Rollinger, Marc Suhrcke, Mark Sculptor and Karl Claxton - - Chapter 4: Fairer Decisions, Better Health for All: Health Equity and Cost-Effectiveness Analysis / Andrew J. Mirelman, Miqdad Asaria, Bryony Dawkins, Susan Griffin and Richard Cookson - - Chapter 5: Economic Evaluation of Social Care and Informal are Interventions in Low-and Middle-Income Countries / Helen Weatherly, Rita Faria, Alexandra Rollinger, Bernard van den Berg, Levision Chiwaula, Pritaporn Kingkaew, Aurelio Mejia, Janet Seeley, Stella Settumba and Sax Sandanam - - PART 3: Health System Issues - Chapter 6: Paying for Performance for Health Care in Low-and Middle-Income Countries: An Economic Perspective / Martin Chalkley, Andrew J. Mirelman, Luigi Siciliani an Marc Suhrcke - - Chapter 7: Public Financial Management and Health Service Delivery: A Literature Review / Yevgeny Goryakin, Paul Revill, Andrew J. Mirelman, Rohan Sweeney, Jessica Ochalek and Marc Suhrcke - - Chapter 8: Demand-Side Financing in Health in Low-Resource Settings / Tim Ensor and Suresh Tiwari - - Chapter 9: A New Approach to Measuring Health Development: From National Income Toward Health Coverage (and Beyond) / Rodrigo Moreno-Serra, Arne Hole and Peter C. Smith - - Case Studies Application of Methods - Chapter 10: Supporting the Development of Health Benefits Packages (HBPs): Principles and Initial Assessment for Malawi / Jessie Ochalek, Gerald Manthalu, Dominic Nkhoma, Finn McGuire, Alexandra Rollinger, Paul Revill, Mark Sculpher, and Karl Claxton - - Chapter 11: Modeling and Economic Evaluation to Inform WHO HIV Treatment Guidelines / Paul Revill. Andrew Phillips, Jeffrey W. Eaton and Timothy B. Hallett - - Chapter 12: Evaluating the 2014 Sugar-Sweetened Beverage Tax in Chile: Observational Evidence from Urban Areas / Ryota Nakamura, Andrew J. Mirelman, Cristóbal Cuadrado, Nicolás Silva, Jocelyn Dunstan and Marc Suhrcke.
Includes bibliographical references and index.
Keywords: Global Health -- Economics; Economics, Medical; Health Policy; Medically Underserved Area; Poverty Areas